Administración racional del patrimonio. Análisis comparado y aplicación extensiva del estándar contenido en materia de criminalidad concursal - Mayer Lux, Laura (2025)
This paper analyses the new criterion of “rational administration of assets”, provided for in the bankruptcy crime of article 463 of the Chilean Penal Code, recently amended by the Economic Crimes Law, No. 21,595 of August 2023. For such purposes, the article compares this standard with other equivalent criterions, such as “orderly economic management” or “diligence in the management of economic affairs”. The paper concludes that, beyond the terminological issue, all these standards point in the same direction. Additionally, the article highlights that the Chilean criterion is not only more precise and adequate in criminal law matters, but can also have a broad scope, capable of extending to crimes such as disloyal administration or fraud against the State.